Pengaruh Kualitas Produk Dan Media Sosial Terhadap Keputusan Pembelian Dengan Citra Merek Sebagai Variabel Intervening Pada Produk Iphone (Studi Kasus Pengguna Produk Iphone Pada Mahasiswa Di Universitas Putra Indonesia "YPTK" Padang) - Mutiara Muliani; Vicky Brama Kumbara; Della Asmaria Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine and analyze the influence of product quality and social media on purchasing decisions with brand image as an intervening variable for iPhone products (A Case Study of iPhone Product Users Among Students at Universitas Putra Indonesia "YPTK" Padang). The population and sample of this study were iPhone users at UPI "YPTK" Padang. Primary data were collected through questionnaires and then analyzed using SEM-PLS (SmartPLS 4.0) to test the measurement and structural models. The results of the study found that Product Quality has a positive and significant effect on Brand Image. Social Media has a positive and significant effect on Brand Image. Product Quality has a positive and significant effect on Product Purchase Decisions. Social Media has a positive but insignificant effect on Purchase Decisions. Brand Image has a positive but insignificant effect on Purchase Decisions. Product Quality has a positive but insignificant effect on Purchase Decisions through Brand Image. Social Media has a positive but insignificant effect on Purchase Decisions through Brand Image